1999
DOI: 10.1071/ea99018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of hand thinning on productivity of Moorpark apricots destined for drying

Abstract: Summary. Thinning at full bloom was compared with thinning at 3 stages of fruit development and the effects on size, total soluble solids level (TSS) and yield of apricots are reported. In 2 seasons separate branches of 9-year-old Moorpark apricot trees were hand-thinned to a density of 1 blossom or fruit per 50 mm of fruiting wood. Times of thinning were at full bloom, 5–15 mm size fruit, stone tip hardening and 21 days post stone tip hardening. These treatments were compared with an unthinned control. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The effect of crop load on SSC has also been reported to differ in other trials. Chemical or hand thinning apricot trees to lower crop loads resulted in no effect on SSC in some trials, whereas it resulted in significant increases in SSC in other trials . In general, more severe thinning increased the difference in SSC.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The effect of crop load on SSC has also been reported to differ in other trials. Chemical or hand thinning apricot trees to lower crop loads resulted in no effect on SSC in some trials, whereas it resulted in significant increases in SSC in other trials . In general, more severe thinning increased the difference in SSC.…”
Section: Resultsmentioning
confidence: 89%
“…Although the effects of maturity of fruit at harvest on consumer preferences have been previously examined, no studies were found on crop load affecting consumer liking of apricot fruit. Crop load has been shown to affect SSC and SSC to affect consumer liking so, intuitively, an increase in consumer liking for fruit from lower crop loads would be expected. In this study, fruit from lower crop load trees were preferred, but not always.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations